Construction products information Importance and influence towards digitalization - Hipólito Sousa (2018)
One of the main challenges of building refurbishment operations is the combination of traditional/ancient technical solutions with current/innovative technologies. In addition to the requirements in terms of aesthetics and compatibility with the preexistence, there are also requirements in terms of functionality, efficiency and durability. This research benefits from the experience of a contractor on rehabilitation strategies, clients demands and work results. Yet, in order to implement innovative processes to improve construction competitiveness and sustainability, there are information gaps and processes that need to be streamlined. Construction information digitalization is found to be a driver to achieve these outcomes. This paper presets a simple case study (but that is representative of the industry practices) of a commonly used product; Gypsum board, using a small sample (3 manufacturers) and developing an analysis focused on the information requirements towards an improved efficiency of the industry.